CAR-OLT score predicts cardiac contraindications to liver transplant and 1-year cardiovascular complications after transplant. (March 2023) - Biolato, M.; Martini, S.; Petti, A.; Galati, F.; Saracco, M.; Tomasello, L.; Liguori, A.; Risso, A.; Marrone, G.; Miele, L.; Avolio, A.W.; Pompili, M.; et al.
Abstract : Background: Accurate pre-Liver Transplant(LT) cardiac risk estimation is paramount to guide graft allocation and to improve post-LT outcome. CAR-OLT-score predicts major 1-year post-LT cardiovascular complications(CVD-Com), but external validation is lacking. We aimed to test the performance of the score in identifying cardiac contraindication(Ca-Con) to LT-listing and to validate CAR-OLT-score to predict major 1-year CVD-Com post-LT. Patients and Methods: We consecutive enrolled all adult cirrhotics who underwent first pre-LT evaluation in Rome-Gemelli-Center(RO-cohort, N=342, from 2015 to 2019) and Turin-Center(TU-cohort, N=302, from 2015 to 2017). The main outcome measures were Ca-Con to listing(after center-specific cardiology work-up) and major 1-year CVD-Com post-transplant(death/hospitalization for CVD event). Discriminative performance of CAR-OLT-score was evaluated by area-under-the-ROC-curve(AUROC) method. Results: Among 644 pre-LT cirrhotics, 23(3.6%) received a Ca-Con to listing (52.2% because of coronary artery disease, CAD). CAD, heart failure and atrial fibrillation were independent predictors of Ca-Con to listing. Among 431 first-LT recipients, 38(8.8%) patients experienced 1-year major CVD-Com (39.5% atrial-fibrillation, 23.7% heart-failure, 21% myocardial infarction). Diabetes, pulmonary hypertension, non-active workers were independent predictors of 1-year major CVD-Com. RO-cohort had higher prevalence of hypertensive, obese, diabetic, alcoholic patients and higher burden of CAD, atrial-fibrillation, heart-failure, peripheral vasculopathy compared with TU-cohort. CAR-OLT-score predicts Ca-Con to listing in RO-cohort (AUROC 0.806) and TU-cohort (AUROC 0.978) and 1-year major CVD-Com in RO-cohort (AUROC 0.746) and TU-cohort (AUROC 0.640). 193(29.9%) candidates had CAR-OLT-score ≤23. This cut-off had 99% NPV for Ca-Con to listing and 95% NPV for 1-year major CVD-Com post-LT. Candidates with CAR-OLT-score ≤23 underwent 18 cardiac-exercise-stress-test, 89 myocardial-perfusion-imaging, 24 dobutamine-stress-echocardiography, 10 coronary-computed-tomography, 17 coronary-angiography pre-listing, with estimated costs of 68.090€. Conclusion: CAR-OLT-score ≤23 identified candidates who can be safely listed without provocative cardiac tests, allowing time and cost savings and we validated CAR-OLT-score as predictor of major 1-year CVD-Com in an Italian cohort of LT recipients.